Performance measurement and accountability in Indonesian Local Government - Akbar, Rusdi (Curtin University, 2011)
Performance measurement and accountability in the management of public sector programs have long been seen as central factors in public management research globally. For more than two decades, in many developed countries, heightened interest in performance measurement in government organisations has held tremendous promise for both academics and practitioners.Despite the global trend, there has been little research on performance measurement and accountability in Indonesia. This paucity exists even though regulations have been in existence for more than a decade requiring government organisations to prepare and submit an 'accountability of performance report‘ as a crucial component of Indonesia‘s public sector reform. This thesis investigates the implementation of performance measurement systems in Indonesia during the first wave of public sector reform. Specifically, it examines factors affecting the development and use of performance indicators in Indonesian local government (ILG).Employing a mixed research methodology, the thesis utilises a combination of a nation-wide survey and follow-up in-depth interviews with local government senior officials who are responsible for preparing performance reports. Specifically, the study explores the experiences and perceptions of government officials regarding the development and use of performance indicators and accountability practices in Indonesian local governments. The research findings contribute not only to the academic literature but also to practical public policy. The results indicate that metric difficulties, technical knowledge, management commitment, legislative requirement, and organisational capacity all have an effect on the development and use of performance indicators and accountability practices in ILG. Legislative requirement and management commitment have the strongest influence.The more contextual reasons and motivations behind the implementation process were also investigated and are illustrated in this thesis. For this purpose, institutional theory was used as the theoretical framework to better explain and understand the issues. The findings revealed that institutional isomorphism did contribute to the process of decision making. All three institutional components of isomorphism-coercive, mimetic and normative pressures-were found in ILG with coercive pressure found to be the strongest influence.The findings of this research have academic implications for scholars in public sector management and practical implications for many different parties, namely: 1) central government; 2) local government; 3) government auditors; and 4) universities. The findings provide an overview of performance measurement and accountability practices in a local government context. Specifically, this thesis provides important evidence regarding factors influencing the development and use of performance indicators, as well as factors hindering the implementation of performance measurement systems. In addition, it reveals the influence of isomorphic pressures in the implementation of performance measurement systems in Indonesia.Results revealed in the thesis are useful in evaluating the success or failure of the past implementation process. More importantly, the findings will be essential in helping to determine current and future policies and to ensure their continued success. This thesis provides analyses on the results of a decade of reform efforts in the area of public sector performance measurement and accountability in Indonesian local governments. With the recently-launched bureaucratic reform marking the second wave of reform (2010-2025) to improve Indonesian government, a reform effort that includes for the first time the vice-president‘s office, research into performance measurement and accountability practices in the first wave of reform (1999-2009) is especially timely.In summary, the significant contributions this thesis makes to performance measurement and accountability literature are threefold. Theoretically it provides a relevant exemplar regarding the application of institutional theory on performance measurement research in a developing country. Methodologically it contributes to the increasing use of mixed-method research. Analytically it provides evidence of the use of partial least squares as a relevant analytical tool. Further, this thesis paves the way for future research in the relatively unexamined area of public sector performance measurement and accountability in Indonesia.